Two New Reference Materials Based on Tobacco Leaves: Certification for over a Dozen of Toxic and Essential Elements - Zbigniew Samczyński; Rajmund S. Dybczyński; Halina Polkowska-Motrenko; Ewelina Chajduk; Marta Pyszynska; Bożena Danko; Elżbieta Czerska; Krzysztof Kulisa; Katarzyna Doner; Paweł Kalbarczyk (The Scientific World Journal)
The preparation, certification, and characterization of two new biological certified reference materials for inorganic trace analysis have been presented. They are based on two different varieties of tobacco leaves, namely, Oriental Basma Tobacco Leaves (INCT-OBTL-5), grown in Greece, and Polish Virginia Tobacco Leaves (INCT-PVTL-6), grown in Poland. Certification of the materials was based on the statistical evaluation of results obtained in a worldwide interlaboratory comparison, in which 87 laboratories from 18 countries participated, providing 2568 laboratory averages on nearly 80 elements. It was possible to establish the certified values of concentration for many elements in the new materials, that is, 37 in INCT-OBTL-5 and 36 in INCT-PVTL-6, including several toxic ones like As, Cd, Hg, Pb, and so forth. The share and the role of instrumental analytical techniques used in the process of certification of the new CRMs are discussed.